A Morphological Analysis Of Derivational Noun In Short Story Of Boscombe Valley Mystery - Ventina, Nita, Drs. Sigit Haryanto, M.Hum, Dr. Dwi Haryanti, M.Hum (2014)
This study studies the derivational noun in short story of Boscombe Valley Mystery. The objective of this study are to describe the formation of derivational noun found in short story of Boscombe Valley Mystery and to identify the morphological conditioned environment which happen in the derivational noun short story of Boscome Valley Mystery. This research is a descriptive qualitative research. The data are in the form of English words which contain derivational noun from English short story in "Boscombe Valley Mystery". Technique of collecting data is documentation. The data are analyzed by reading the English short story in "Boscombe Valley Mystery", classifying the word or sentence to the English words which contain English derivational noun, and identifying the derivational noun process that occurs on English words. The result of this study shows the formation from verb into noun are 140 words, there are consist of derived from suffix (-ment) 20 words, derived from suffix (-ion) 40 words, derived from suffix (-ation) 20 words, derived from suffix (-er) 16 words, derived from suffix (-or) 13 words, derived from suffix (-ence) 9 words, derived from suffix (-ance) 9 words, derived from (-age) 4 words, derived from suffix (-al) 5 words. The formation adjective into noun are 39 words, there are consist of derived from suffix (-ity) 17 words, derived from suffix (- ation) 5 words, derived from suffix (-ion) 3 words, derived from suffix (-ness) 14 words. The formation from noun into noun are 5 words, derived from suffix (-er) are 5 words, and the morphological conditioned environment are 3 words derived from verb with suffix -age, -ation, and -ion.